All the divine names and titles in the Bible a unique classification of all scriptural designations of the three persons of the Trinity - Lockyer, Herbert, 1886- (Grand Rapids, MI Zondervan, 1975)
Includes bibliographical references and index.
Brethren writer.
Keywords: Names of God